Why science and art creativities matter : (re-)configuring STEAM for future-making education - Burnard, Pamela; Colucci-Gray, Laura (Leiden, The Netherlands ; Boston : Brill Sense, 2020)
Why Science and Arts Creativities Matter is a ground-breaking text which significantly extends current understandings of STEAM and debates about individuation of disciplines vis-à-vis transdisciplinary theory. Drawing upon posthumanism, new materialism and enactivism, this collection of chapters aims to dwell further into the ways in which we come to know in relationship with the world. The text draws together a wide set of approaches and points of views to stimulate dialogue and awareness of the different ways in which we can extend the repertoire of human faculties for thinking and experiencing the world. A unique invitation is shared with readers to develop greater understanding of the contribution of education across the arts and sciences and to re-imagine our collective futures. This book is a unique and timely volume that opens up several new lines of enquiry and arguments on STEAM education. It rebalances and readdresses the current emphasis in the literature around STEAM as another, newer opportunity to teach content. Instead, it brings a more specific focus on an entwining of contemporary theorists – putting theory to work – to extend the means for understanding and cultivating science and arts creativities, and make explicit key connections with the materiality of practices. This new go-to text offers a demonstration of how the latest research and theoretically engaged thinking (thinking through theory) on STEAM education can be put to work in practice. Contributors are: Ramsey Affifi, Sofie Areljung, Chris Brownell, Pamela Burnard, Kerry Chappell, Laura Colucci-Gray, Carolyn Cooke, Kristóf Fenyvesi, Erik Fooladi, Cathy Francis, Lindsay Hetherington, Anna Hickey-Moody, Christine Horn, Tim Ingold, Riikka Kosola, Zsolt Lavicza, Elsa Lee, Saara Lehto, Danielle Lloyd, James Macallister, Caroline Maloney, Tessa Mcgavock, Karin Murris, Lena Nasiakou, Edvin Østergaard, Anne Pirrie, Hermione Ruck Keene, Ruth Sapsed, Diana Scherer, Pallawi Sinha, Margaret Somerville, Keiren Stephenson, Carine Steyn, Jan Van Boeckel, Nicola Walshe, Olivier Werner, Marissa Willcox, and Heather Wren.
(Re-)Configuring STEAM in Future-Making Education / Laura Colucci-Gray and Pamela Burnard -- Positioning STEAM in Future-Making Education -- Introduction to Part 1 / Pamela Burnard and Laura Colucci-Gray -- Where Science Ends, Art Begins? / Anne Pirrie -- Becoming Bird / Margaret Somerville, Tessa McGavock and Keiren Stephenson -- Posthuman De/Colonising Teacher Education in South Africa / Karin Murris -- Between Will and Wildness in STEAM Education / Ramsey Affifi -- Why Does Science Matter? -- Introduction to Part 2 / Pamela Burnard and Laura Colucci-Gray -- Developing an Ecological View through STEAM Pedagogies in Science Education / Laura Colucci-Gray -- Listening in Science Education / Edvin Østergaard -- Science-Arts as Verbs / Sofie Areljung -- Why Do the Arts Matter? -- Introduction to Part 3 / Pamela Burnard and Laura Colucci-Gray -- Reconfiguring STEAM through Material Enactments of Mathematics and Arts / Pamela Burnard, Pallawi Sinha, Carine Steyn, Kristóf Fenyvesi, Christopher Brownell, Olivier Werner and Zsolt Lavicza -- STEAM Education, Art/Science and Quiet Activism / Anna Hickey-Moody, Christine Horn and Marissa Willcox -- Embracing the Serpent / James MacAllister -- Linking the Missing Links / Jan van Boeckel -- STEAM Reconfigurings in Practice -- Introduction to Part 4 / Pamela Burnard and Laura Colucci-Gray -- Creative Pedagogy and Environmental Responsibility / Lindsay Hetherington, Kerry Chappell, Hermione Ruck Keene and Heather Wren -- Learning Mathematical Concepts as a Whole-Body Experience / Kristóf Fenyvesi, Saara Lehto, Christopher Brownell, Lena Nasiakou, Zsolt Lavicza and Riikka Kosola -- STEM to STEAM as an Approach to Human Development / Nicola Walshe, Elsa Lee, Danielle Lloyd and Ruth Sapsed -- Taste as Science, Aesthetic Experience and Inquiry / Erik Fooladi -- On Sensorial Experiences at the Beach / Catherine Francis -- On Methodological Accounts of Improvisation and “Making with” in Science and Music / Carolyn Cooke -- Un-Conclusions / Pamela Burnard and Laura Colucci-Gray -- What Knowledge Do We Need for Future-Making Education? / Tim Ingold.
Includes index.
Description based on print version record.
Keywords: Science -- Study and teaching